Kebijakan Penegakan Hukum Pidana Dalam Penanggulangan Tindak Pidana Politik Uang Terhadap Penyelenggaraan Pemilu - Sari, Ratna Kumala; Maulidah, Khilmatin; Kurnia, Kamal Fahmi (Universitas Sang Bumi Ruwa Jurai, 2025)
The implementation of general elections (Pemilu) is an important indicator in a democratic system because people can participate in determining their political choices for the country and its government. This study aims to analyse how criminal law enforcement is carried out in overcoming criminal acts of money politics against the implementation of current elections? and how is criminal law enforcement in preventing criminal acts of money politics against the implementation of elections in the future? Data was collected through normative legal research methods by inventorying positive law and literature, then analysed using a qualitative approach. The results of the study indicate that law enforcement against the practice of money politics in general elections (Pemilu) has problems, especially in terms of regulation, namely related to the weaknesses of the Election Law which can cause certain legal subjects to escape from the criminal trap of the Election Law. The Election Law only regulates the prohibition of money politics practices to givers or people who promise. While the recipient is not strictly regulated